The influence of contextual information regarding the breakdown of relationships and perpetrator-target sex composition on perceptions of relational stalking - Scott, A.; Duff, S.; Sheridan, Lorraine; Rajakaruna, N. (Routledge, 2018)
The present study examines the influence of prior relationship (with contextual information regarding the breakdown of the relationship) and perpetrator-target sex composition on perceptions of relational stalking. The study employed an experimental 7 × 2 independent measures design, and the sample comprised 1,260 members of the community residing in Australia, the United Kingdom and the United States. Participants received one of 14 versions of a hypothetical scenario and responded to scale items concerning the situation described. The situation was perceived to be most serious when the perpetrator was a stranger or a physically violent ex-partner and least serious when the perpetrator was an ex-partner of an unfaithful target. Scenarios involving a male perpetrator and a female victim were also perceived to be more serious than scenarios involving a female perpetrator and a male target. It is apparent therefore that the context of the relationship breakdown and the sex of the perpetrator and target significantly influence perceptions of relational stalking.